Dyskurs (post)konwencjonalnej tożsamości wobec merkantylistycznej natury globalizującego się świata - Jastrząb, Patryk (Kultura-Społeczeństwo-Edukacja, 2014)
In this article I described the idea of globalization, but I abandoned a strictly scientific analysis and treated the subject more contemplatively. I described not only the process, but also the values (connected with the culture of instant gratification, globalization and the cultural homogenization) and the orientation connected with it (consumerism, commoditization of human life) which shape the surrounding reality as well as ourselves. The question of identity, which is constantly shaping, is significant in this context. It is, just as globalization, fluid, unspecified and ambivalent. I endeavour to prove the hypotheses by adducing sociological, cultural and philosophical classic writers. The very last ones – fairly unexpectedly – become crucial to me and they let me analyse the human nature in postmodern reality holistically.